Adventures in Archaeology : The Wreck of the Orca II and Other Explorations - Capelotti, P. J. (Peter Joseph), 1960- (Book collections on Project MUSE., 2018)
This collection of essays, written over nearly 25 years, traces the development of the archaeologies of shoreline, sea, air, and space, to reveal how the expansion of human culture has created unique archaeological signatures written on the global landscape, and how the cultural history of humans can be read from these material transformations.